Nobody to Play With? The Implications of Leisure Coordination - Stephen P. Jenkins; Lars Osberg (Institute for the Study of Labor (IZA), 2003)
We hypothesize that an individual?s time use choices are contingent on the time use choices of others because the utility derived from leisure time often benefits from the presence of companionable others inside and outside the household. We develop a model of time use, and demonstrate that its consistency with the behaviour of British working couples in the 1990s. We present evidence of the synchronisation of working hours by spouses and report estimates indicating that propensities to engage in associative activity depend on the availability of Suitable Leisure Companions outside the household. Our results indicate the importance of externalities in the working time decisions of individuals.
Keywords: D13; J22; I31; 330; time use; leisure; labour supply; work hours; Freizeitverhalten; Arbeitsangebot; Zeitallokation; Konsuminterdependenz; Haushaltsökonomik; Theorie; Schätzung; Großbritannien